Influence of Aluminium Waste Chips Content from the Machining Technology in the Batch on the Final Properties of the AlSi7Mg0.3 Alloy Casts - Vlach, Tomáš; Cais, Jaromír; Horký, Roman (Manufacturing Technology Journal, 2024)
The aim of the research was to assess the influence of additions of different proportions of alumini-um waste chips from the machining technology on the melt quality and final properties of AlSi7Mg0.3 alloy casts. All casts were created using by gravity casting technology into preheated metal mold. The first cast was a pure AlSi7Mg0.3 alloy, followed by other samples with contents of 10, 30, 50, 70 wt.% of aluminum waste chips in the batches. All the samples were subjected to the Brinnel hardness and Vickers microhardness of solid solution of α(Al). Also, Density index was measured. At the end of research, the microstructures of the samples were analyzed using a Laser Confocal Microscope Olympus Lext OLS 5000.
Keywords: Al-Si alloys; Casts; Aluminium waste; Waste chips; Density index